6k-6=5k-2

Simple and best practice solution for 6k-6=5k-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6k-6=5k-2 equation:


Simplifying
6k + -6 = 5k + -2

Reorder the terms:
-6 + 6k = 5k + -2

Reorder the terms:
-6 + 6k = -2 + 5k

Solving
-6 + 6k = -2 + 5k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-5k' to each side of the equation.
-6 + 6k + -5k = -2 + 5k + -5k

Combine like terms: 6k + -5k = 1k
-6 + 1k = -2 + 5k + -5k

Combine like terms: 5k + -5k = 0
-6 + 1k = -2 + 0
-6 + 1k = -2

Add '6' to each side of the equation.
-6 + 6 + 1k = -2 + 6

Combine like terms: -6 + 6 = 0
0 + 1k = -2 + 6
1k = -2 + 6

Combine like terms: -2 + 6 = 4
1k = 4

Divide each side by '1'.
k = 4

Simplifying
k = 4

See similar equations:

| X=6.8-.2y | | 5x-180=0 | | -(X+2)=3X-4 | | 6x+36=3x+81 | | 19x-2(x+10)=12 | | N+12=12+7 | | 3x-4/3+2x-8/4=5x+8/2 | | 3(2x+1)=34 | | 4/9x1/9 | | 1x-33=2+12 | | 5x+3(x+2)=19 | | 4x+10=10+4x | | 3z+2=6z-4z | | 4t^2-8t/(18-9t) | | 4+1/7+1/2 | | 18-n=9+3 | | -3.5x=12.25 | | 21-6=11 | | 7c=-42 | | 2+3x=7+3x | | 6x+9x-23=115-8x | | 8x+35=47 | | -4(3t-5)+8t=7t-5 | | 8/h=288 | | 10+17c+13c= | | -x-4=-13 | | b-24=16 | | 2/1/3+1/1/4 | | 19x+6y=71.90 | | x=4x-8/(x-4)(x+1) | | 4.2x-3=0.5 | | -9(x+12)=8(4+5x)-4x |

Equations solver categories